Faktor-Faktor Yang Mempengaruhi Kepuasan Pengunjung Agrowisata Taman Hati Farm Kota Tasikmalaya - Nurhayati, Nurhayati; Fitriadi, Budhi Wahyu; Sundari, Ristina Siti (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Visitor satisfaction can be defined as the level of feelings a person feels after comparing perceived performance with their expectations. This reflects the emotional response to the experience gained when consuming a product or service. This research aims to analyze the factors that influence the satisfaction of Taman Hati Farm agrotourism visitors. Agrotourism, as a form of tourism that combines agricultural and recreational elements, is increasingly popular among the public. This research uses a form of descriptive research with a quantitative approach. The sampling method was nonprobability sampling and purposive sampling with the criteria of Taman Hati Farm Agrotourism visitors over 15 years as many as 97 samples. Data was collected through a visitor survey to agrotourism at Taman Hati Farm agrotourism which was carried out from March to May. The data obtained was analyzed using the multiple linear regression method to determine the influence of each variable on visitor satisfaction. The research results show that facilities and prices have a significant influence on visitor satisfaction, while service quality does not show a significant influence on visitor satisfaction at Taman Hati Farm Agrotourism. The most dominant influencing factor is the price factor.